Vertex epidural hematoma: An analysis of a large series - Ramesh, Vengalathur; Kodeeswaran, Marappan; Deiveegan, Kunjithapatham; Sundar, Venkataraman; Sriram, Kuchalambal (Asian Journal of Neurosurgery, 2017)
Context: Vertex epidural hematoma (VEDH) is uncommon. A high index of suspicion is required to suspect and diagnose this condition, and the surgical management is a challenge to neurosurgeons. There are only isolated case reports or small series of VEDH in the literature. Aims: We have tried to analyze a large series of VEDH seen in our institute. Settings and Design: Retrospective observational study. Subjects and Methods: This is an analysis of case records of patients with VEDH during 17 years period from 1995 to 2012. Statistical Analysis Used: Nil. Results: Twenty nine cases of VEDH encountered over a period of 17 years have been analyzed, including 26 males and 3 females. Majority were due to road accidents. Headache, papilledema and lower limb weakness have been the major presenting features in these cases. The diagnosis was by direct coronal computerized tomography (CT) scan in most of them. Majority were managed conservatively with observation and serial imaging. Four patients who had large VEDH with altered sensorium were managed surgically. The source of bleeding was mainly from superior sagittal sinus. Conclusions: VEDH has to be suspected when a patient presents with impact over the vertex and features of raised intracranial pressure. Direct coronal CT or magnetic resonance imaging is useful in the diagnosis. Surgery is required when the patient develops progressive deterioration in sensorium and/or with the hematoma volume more than 30 ml. The present series of 29 cases is the largest reported so far.
Keywords: Extradural hematoma; vertex epidural hematoma; vertex extradural hematoma